Geophilomorph centipedes (Chilopoda) from termite mounds in the northern Pantanal wetland of Mato Grosso, Brazil - Pereira, Luis Alberto (2007)
Of two species of geophilomorph centipedes collected above high waters in termite mounds in the Pantanal of Mato Grosso, one (Schendylops inquilinus) is described here as new; the other (Aphilodon angustatus Silvestri, 1909) is redescribed.